Beneficial effect of polaprezinc on cardiac function post-myocardial infarction: A prospective and randomized clinical trial. Issue 10 (March 2019) - Yoshikawa, Fumitsugu; Nakajima, Tetsu; Hanada, Masaharu; Hirata, Kazuo; Masuyama, Tohru; Aikawa, Ryuichi
Abstract: Background: Polaprezinc is clinically used for the treatment of gastric ulcers. It induces the mobilization of mesenchymal stem cells and the mRNA expression of insulin-like growth factor-1 in vascular endothelial cells in order to protect injured gastric tissue or skin. Methods: The current study population included 50 patients with primary acute myocardial infarction (AMI). After percutaneous coronary intervention, the subjects were randomly divided into 2 groups, namely, the nonpolaprezinc and polaprezinc groups. Peripheral blood and urinary samples were collected in a specific time to analyze zinc concentration, cardiac enzymes, and the levels of the inflammation marker interleukin-6. To evaluate the cardiac function, echocardiography was performed upon admission to the hospital and at 9 months post-AMI. Results: The urine and blood zinc levels of the polaprezinc group were higher compared with those of the non-polaprezinc group at 8 days after percutaneous coronary intervention. The mean interleukin-6/maximal creatine phosphokinase level was significantly reduced in the polaprezinc group (0.024 [0.003–0.066] vs. 0.076 [0.015–0.212], respectively; P  = .045). In addition, echocardiography revealed that the ejection fraction of the nonpolaprezinc group was not significantly increased between day 3 and 9 months post-AMI (53 [49–60.8] vs. 59.5 [52–69.3], respectively; P  = .015). However, a significant increase was detected in the ejection fraction of the polaprezinc group at the 2 time points (54 [51–57] vs. 62 [55–71], respectively; P  < .01). Conclusions: The results of the present study suggest that polaprezinc has an anti-inflammatory effect and improves cardiac function after AMI.